Prime broking default at the national stock exchange - Varma, J. R. (SAGE business cases., 2020)
The case describes a puzzling situation where a member default caused significant losses to National Securities Clearing Corporation Limited (NSCCL), the central counterparty (CCP) of India's largest equity derivatives exchange, although there was no significant movement in the relevant market prices. It highlights the risks arising from collateral, liquidity, and concentration, even when the market risk environment is benign. The case shows how market participants can use a combination of exchange-traded options to replicate financial transactions beyond the typical remit of a CCP. For example, these synthetic structures can blur the line between providing a settlement guarantee, which is the core function of a CCP, and giving credit enhancement to a loan against shares, which is outside the purview of a CCP. The wrong-way risk may crop up unexpectedly unless the CCP is continuously on its guard. The case also illustrates the issues of operational risk in the default management process. All the mathematical models used for managing market risk may function flawlessly, and yet, the CCP can be exposed to substantial losses. The only consolation for NSCCL was that its default funds were large enough to absorb this loss, without affecting market confidence in the CCP.